The Performance Measurement System of the Kutawaringin Sub-District Government: An Analysis Based on Key Performance Indicators - Burnama, Satryadi; Ali, Mochammad Mukti (Dinasti International Journal of Management Science, 2025)
This study aims to analyze the alignment of the Key Performance Indicators (KPIs) used by Kutawaringin Sub-district with its institutional functions as mandated by regulatory frameworks and outcome-based public sector performance management theory. The main issue addressed is the misalignment between the existing KPIs and the sub-district's coordinative role. A qualitative approach with a framework analysis design was employed, using in-depth interviews, participatory observation, and document review conducted between January and July 2025. The findings reveal that dominant KPIs, such as the Community Satisfaction Index and the number of rapidly developing villages, focus heavily on administrative outputs and fail to capture the sub-district’s cross-sectoral coordination outcomes. Key obstacles include inconsistent indicators, weak inter-agency collaboration, and the absence of technical guidance. As a response, an inter-agency forum proposed the Sub-district Synergy Score as a more relevant indicator aligned with the sub-district’s substantive mandate. Although still in early adoption, this indicator is currently being piloted for medium-term performance assessment. The study emphasizes the need to strengthen collaborative governance and ensure the substantive validity of performance indicators, thereby contributing to the development of outcome-oriented KPI frameworks for non-sectoral public organizations in Indonesia, particularly at the sub-district level.